Fate, behaviour and weathering of priority HNS in the marine environment: An online tool. Issue 1 (15th October 2016) - Cunha, Isabel; Oliveira, Helena; Neuparth, Teresa; Torres, Tiago; Santos, Miguel Machado
Abstract: Literature data and data obtained with modelling tools were compiled to derive the physicochemical behaviour of 24 priority Hazardous and Noxious Substances (HNS), as a proxy to improve environmental, public health and political issues in relation to HNS spills. Parameters that rule the HNS behaviour in water and those that determine their distribution and persistence in the environment, such as fugacity, physicochemical degradation, biodegradation, bioaccumulation/biotransformation and aquatic toxicity, were selected. Data systematized and produced in the frame of the Arcopol Platform project was made available through a public database (http://www.ciimar.up.pt/hns/substances.php ). This tool is expected to assist stakeholders involved in HNS spills preparedness and response, policy makers and legislators, as well as to contribute to a current picture of the scientific knowledge on the fate, behaviour, weathering and toxicity of priority HNS, being essential to support future improvements in maritime safety and coastal pollution response before, during and after spill incidents. Highlights: Fate, behaviour and weathering of priority HNS in marine environments are addressed. Environmental and public health issues in relation to HNS spills are discussed. Physicochemical behaviour is derived through mathematical tools and literature data. Data produced are made available through a public online database. Database can assist relevant bodies involved in HNS spills preparedness and response.